Предмет: Алгебра,
автор: JackPirs
1) Упростите выражение
2) Решите систему уравнений
Ответы
Автор ответа:
0
1
(√a+√b)/(√a-√b)(√a+√b)=1/(√a-√b)
(a-b)(a+b)/√a(a+b)=(a-b)/√a
1/(√a-√b)-(a-b)/√a=(√a-a√a+b√a+a√b-b√b)/√a(√a-√b)
2
(√x-√y)(√x+√y)=120
√x-√y=4
√x+√y=30
2√x=34
√x=17
x=289
√y=13
y=169
(√a+√b)/(√a-√b)(√a+√b)=1/(√a-√b)
(a-b)(a+b)/√a(a+b)=(a-b)/√a
1/(√a-√b)-(a-b)/√a=(√a-a√a+b√a+a√b-b√b)/√a(√a-√b)
2
(√x-√y)(√x+√y)=120
√x-√y=4
√x+√y=30
2√x=34
√x=17
x=289
√y=13
y=169
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Физика,
автор: elkurbanov07
Предмет: Русский язык,
автор: erasylbaratov
Предмет: Математика,
автор: ceeenna10
Предмет: Обществознание,
автор: allaantonova97